PRAKTEK KERJA LAPANGAN BISNIS USAHA WARUNG MAKAN KELUARGA YANG KREATIF, BERKUALITAS DAN BERORIENTASI SOSIAL ( Studi kasus di Pawon Mbak Iik Sidokerto) - Allisa Putri Setyadi; Dewi Riza Vahlevi (ICO EDUSHA, 2021)
Business is a business managed by individuals or groups by providing products or service to the public that are profit oriented. Now, one of the business that has great potential global economy is the food business. According to data Badan Pusat Statistik (BPS), in quarter II Indonesian food and beverage industry in 2021 increased in the amount of 2,95 % in yoy from the third previous quarter[1]. Food business divided in many phase like a restaurant, angkringan, café, and food stalls (Warung makan). Food stalls (warung makan) is a place of business that provide a quality variey food menu and economical price and Pawon Mbak iik is one type of food stalls business in Sidokerto, Buduran, Sidorjo, East Java. Pawon mbak iik is food stalls which is not only profit oriented, but also has social purpose for society. The methods of research uses a qualitative analysis descriptive. The purpose of the research is (1) for know the brief profile of the Pawon Mbak iik establishment, (2)for know the success strategy of Pawon Mbak iik in managing their business, (3) for know activity and product in Pawon Mbak iik, (4) for know for day to day operational activity. Keywords : Analysis, Business, Food, Profit, Social, Strategy, Pawon Mbak iik References Alfi yuda, Pengertian Bisnis, Tujuan, Fungsi, Jenis, dan Manfaat yang diperoleh, diakses dari https://m.bola.com/ragam/read/4588305/pengertian-bisnis-tujuan-fungsi-jenis-dan-manfaat-yang-diperoleh-page5, pada tanggal 30 November 2021, pukul 15.30 wib Agung Prasetyo, Pengertian Penelitian Deskriptif Kualitatif, Mahasiswa Skripsi Wajib Tahu, diakses dari https://www.linguistikid.com/2016/09/pengertian-penelitian-deskriptif-kualitatif.html?m=1, pada tanggal 30 November 2021, pukul 17.00 wib Daya.id, Pengertian Bisnis Menurut Para Ahli Beserta Unsur-Unsurnya, diakses dari https://www.daya.id/usaha/artikel-daya/pengembangan-diri/pengertian-bisnis-menurut-para-ahli-beserta-unsur-unsurnya, pada tanggal 30 November 2021, pukul 15.40 wib Reni Lestari, 2021, Kemenperin Patok Pertumbuhan Industri Mamin 5 persen, diakses dari https://m.bisnid.com/amp/read/20210906/257/1438655/2021-kemenperin-patok-pertumbuhan-industri-mamin-5-persen, pada tanggal 30 November 2021, pukul 15.00 wib